REVIEW OF SHARIA ECONOMIC INSTITUTION PRODUCTS ON SHARIA HOSPITAL - Yasmeenela, Moniq (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
The development of Islamic hospitals in Indonesia from year to year has increased very significantly. This condition shows that the enthusiasm of the people to seek treatment in Islamic hospitals is getting stronger in this case, it gets an indicator of the high awareness of the people to get health and blessing services. Therefore, a standard or guideline for Islamic hospitals is needed in implementing, measuring and assessing the quality of services and management of hospital management in accordance with Islamic sharia principles, so that Islamic hospitals can provide guarantees of service in accordance with sharia, saving Islamic faith and applying management based sharia.